TRANSACTIONAL LEADERSHIP: IMPROVING SATISFACTION, PERFORMANCE, AND MOTIVATION OF THE EMPLOYEES AT PD. HOLLYWOOD - Nadya Anindhita Radityani; Jerry Marcellinus Logahan (Lembaga Penelitian Universitas Trisakti, 2018)
The objective of this research is to find out about the impact/influence of Leadership Transactional on Employees Satisfaction, Employees Performance, and Motivation at PD. Hollywood. The data are acquired by spreading questionnaires to 46 employees of PD. Hollywood. In this research was using simple and multiple regression method. Thus, in this study writer went to the field, acting as an observer and observed the symptoms and record it in the observational record with no attempt to manipulate the variables. The result are showed that leadership transactional partially and simultaneously have a positive and significant impact/influence on employees satisfaction and motivation, while employee performance has no correlation with leadership transactional. Therefore, automatically there is no significant impact/influence between leadership transactional and employee performance. (NAR)